Waste Transportation System Optimization on Azzahara Material Recovery Facility (MRF) Bengkulu City - Satria, Rendra; Artama, Putu; Hermana, Joni (IPTEK Journal of Proceedings Series, 2015)
Bengkulu city as the capital city of Bengkulu province, in 2013 had a population of 334.529 inhabitants, with waste generated at 10,003.59 m3 / day. Coverage of waste management services in the city of Bengkulu has recently reached 33.01% or 331.29 m3 / day of the total waste. The effectiveness and efficiency waste transport system will increase the amount of waste transported and more communities are underserved. This research aims to improve the coverage of waste service by waste transportation system optimization. Analysis of optimization solid waste transportation system implemented by creating a network problem model and linear programming problem, generate the decision of how many trip of each conveyance and obtain maximum volume of waste transported